2006
DOI: 10.1590/s1517-86922006000600012
|View full text |Cite
|
Sign up to set email alerts
|

Influência da suplementação aguda e crônica de creatina sobre as concentrações sanguíneas de glicose e lactato de ratos Wistar

Abstract: Estudos recentes sugerem que a suplementação de creatina pode interferir com a captação de glicose e a produção de lactato durante a atividade física. O objetivo deste estudo foi investigar os efeitos da suplementação aguda (5g.kg¹ durante uma semana) e crônica (1g.kg¹ durante oito semanas) de creatina sobre as concentrações sanguíneas de glicose e lactato de ratos sedentários e exercitados (natação a 80% da carga máxima tolerada). Setenta e dois ratos Wistar machos (240 ± 10g) foram utilizados e divididos igu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…Taken in aggregate, these results for pro-oxidant markers underscore the findings of Sjodin et al [36] and Souza et al [37], that is, predominantly aerobic exercise causes increased oxygen flow in the mitochondria and approximately five percent of this oxygen is not completely reduced, thereby forming ROS.…”
Section: Discussionsupporting
confidence: 83%
“…Taken in aggregate, these results for pro-oxidant markers underscore the findings of Sjodin et al [36] and Souza et al [37], that is, predominantly aerobic exercise causes increased oxygen flow in the mitochondria and approximately five percent of this oxygen is not completely reduced, thereby forming ROS.…”
Section: Discussionsupporting
confidence: 83%
“…The animals in the TCr and T groups showed decreased body mass relative to the animals of the C and CCr groups. Creatine supplementation has been shown to produce contradictory effects on the change in body mass, as some authors have demonstrated an increase in body mass (Volek et al, 2004;Souza et al, 2006) and others have observed no change in body mass (Louis et al, 2003;Franco et al, 2007). Therefore, our hypothesis was that the observed body weight loss of the animals was not due to creatine supplementation but was solely a result of exercise.…”
Section: Discussionmentioning
confidence: 89%
“…Some authors have reported that creatine supplementation may modify the use of energetic substrates, such as glucose and lactate, and possibly improve physical performance during extended exercises that preferentially use aerobic metabolism (Bembem et al, 2005;Souza et al 2006;Khanna & Manna, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study involving adult male Wistar rats submitted to low-intensity and exhaustive swimming exercise, lactate concentrations were found to be lower in trained animals than in sedentary animals 16 . After 8 weeks of swimming exercise at 80% of maximum load, a reduction in blood lactate concentration was identified when compared to the group of sedentary animals 17 . The divergences between these studies and the present study are probably due to differences in the experimental protocols.…”
Section: Discussionmentioning
confidence: 97%